Analisis strategi perpustakaan Politeknik Caltex Riau (PCR) dalam mendukung Kegiatan literasi Informasi - Indriyeni Indriyeni; Nurasmi; Yuli Astuti (Jurnal Gema Pustakawan, 2023)
Information literacy skills are a fundamental problem facing Indonesia at the moment, the low information literacy index rate is a big homework that must be resolved, especially in library institutions which have one of the functions of educating the nation's life or making a literate society. To realize this, the library needs to design a precise strategy in managing its library. The purpose of this study was to describe the strategy analysis of the PCR Library in supporting information literacy activities using SWOT analysis. The method used is a qualitative method with a descriptive approach. The results of the research are that this research can map the external and internal environmental factors of the PCR Library related to library strategy in supporting information literacy activities using SWOT analysis and the results of the SWOT matrix analysis obtained six strategic components that can be used as input for future planning programs which consist of 2 S-O strategies, namely: 1. Increasing collaboration in utilizing existing collections so that they are more efficient (S.3.-O.1.) and 2. Optimizing IT-based services because users have IT skills (S.5.-O.3.), 1 S-T strategy namely, Improving library quality recognition for example by library accreditation (S.6.-T.1.), 2 W-O strategies namely: 1. Adding human resources by utilizing the available budget (W.3.-O.4.), 2. Adding journal collections (W.5.-O.4.). and 1 W-T strategy, namely: Developing the vision and mission of the library (W.1.-T.1).